Photosynthetic response to low and high light of cacao growing without shade in an area of low evaporative demand (2018)
Cacao (Theobroma cacao L.) breeding programmes in Ecuador have focused on obtaining high-yield clones with improved disease resistance. Cacao clones should also have photosynthetic characteristics which support increased productivity. Regarding the weather conditions at the coast of Ecuador, where most of the year there are overcasts and low air evaporative demand, there is the possibility to grow cacao without overhead shade. This study focused on the photosynthetic response at two different photosynthetic photon flux densities (PPFD) of Ecuadorian cacao clones. Seven-year old cacao clones were evaluated: eight clones of Nacional type and two commercial clones (CCN 51 and EET 103), used as controls. All clones showed an increase of 35 % on average in net photosynthetic rate (A)with increasing PPFD from the light saturation point for cacao (i.e. 400 µmol m-2 s-1) to high values (1000 µmol m-2 s-1). Such light responsiveness in A has not been reported before. Higher A was associated with higher apparent electron transport rate, while high stomatal conductance was maintained under both PPFD conditions. Under high PPFD, low non-photochemical quenching values were found, suggesting low energy dissipation. All clones showed high maximum quantum yields of PSII (Fv/Fm), suggesting the absence of damage of the photochemical system.